Quranic-based concepts: verse relations extraction using Manchester OWL syntax - Yauri, Aliyu Rufai; Abdul Kadir, Rabiah; Azman, Azreen; Azmi Murad, Masrah Azrifah (IEEE, 2012)
In recent years, there is global demand for Islamic knowledge by both Muslims and non-Muslims. This has brought about number of automated applications that ease the retrieval of knowledge from the holy books. However current retrieval methods lack semantic information they are mostly base on keywords matching approach. In this paper we have proposed a Model that will make use of semantic Web technologies (ontology) to model Quran domain knowledge. The system will enhance Quran knowledge by enabling queries in natural language.